Real‐World nivolumab dosing patterns and safety outcomes in patients receiving adjuvant therapy for melanoma - Wolfram Samlowski; Nicholas J. Robert; Liwei Chen; Brad Schenkel; Catherine Davis; Andriy Moshyk; Srividya Kotapati; Tayla Poretta; Jeffrey S. Weber (Cancer Medicine)
Abstract Background Nivolumab at a dose of 480 mg every 4 weeks (Q4W) is approved for the adjuvant treatment of melanoma. However, real‐world data on this regimen are limited in this setting. Methods This retrospective observational study utilized data from the US Oncology Network iKnowMed electronic health record database and patient medical charts. Eligible patients were diagnosed with melanoma and received adjuvant nivolumab monotherapy from March to August 2018. Patients were grouped by dosing regimen: cohort 1 (C1), de novo nivolumab 480 mg Q4W; cohort 2 (C2), switched to nivolumab 480 mg Q4W after nivolumab 240 mg or 3 mg/kg every 2 weeks (Q2W); cohort 3 (C3), de novo nivolumab 3 mg/kg Q2W; or cohort 4 (C4), de novo nivolumab 240 mg Q2W. Patients were followed for up to 12 months. Duration of therapy and safety/tolerability were assessed. Results One hundred ninety‐one patients were included (C1, n = 40; C2, n = 74; C3, n = 22; C4, n = 55). Duration of therapy was relatively consistent across cohorts (median, 10.3 months; range, 8.3–10.7). Likewise, proportions of patients experiencing treatment‐related adverse events (TRAEs) were similar (range, 54.5%–60.1%), as were the most common events (fatigue, rash, diarrhea, hypothyroidism, nausea, and pruritus). However, proportions experiencing ‘significant’ TRAEs varied between cohorts. Proportions discontinuing treatment were relatively consistent across cohorts. Propensity score matching and sensitivity analyses generally supported the unadjusted findings. Conclusions Real‐world safety profiles of nivolumab 240 mg Q2W and 480 mg Q4W were similar, and both were comparable to the well‐documented safety of weight‐based dosing (3 mg/kg Q2W), further supporting their approval and use in the adjuvant setting for melanoma.